Relationships between Smoking, Age, Body Mass Index, and Abstinence with DNA Fragmentation Index in Male Infertile Patients - Ediningtyas, Atifa Nadira; Laqif, Abdurahman; Melinawati, Eriana; Respati, Supriyadi Hari (Journal of Maternal and Child Health, 2022)
Background: Low birth weight (LBW) is defined as a newborn baby weighing less than 2500 grams. Low birth weight is a serious condition in developing countries. The impact of cigarette smoke on pregnant women who are exposed to cigarette smoke is at a higher risk of complications, such as miscarriage, premature birth, or babies born with low weight. This study aims to analyze the relationship between exposure to secondhand smoke and low birth weight. Subjects and Method: This research is a systematic review and meta-analysis by systematically reviewing primary articles from Pubmed, Google Scholar, Scient Direct and Springerlink by selecting articles published in 2012-2022. The articles searched using PICO were P: Pregnant women, I: exposed to cigarette smoke, C: not exposed to cigarette smoke, O: low birth weight. Keywords "Exposure to smoking pregnant women" OR "Expectant mother" OR "Pregnancy women" OR "Exposed to cigarettes" OR "Secondhand smoke exposure" OR "Cigarette smoke expo- sure" AND "Low birth weight" OR "Low weight babies" AND “Case control” AND “Adjusted odds ratio”. Articles used PRISMA flow diagrams and analyzed using Review Manager 5.3. Results: There were nine articles analyzed consisting of Nepal, Morocco, Ethiopia, Sierra Leone, India, Indonesia and China. Meta-analysis showed that cigarette smoke exposure increased the risk of low birth weight and was statistically significant (aOR = 2.19; 95% CI = 1.58 to 3.03; p < 0.001). Conclusion: Exposure to cigarette smoke increases the risk of weight gain in LBW infants by 2.19 times compared to not exposed to cigarette smoke. Keywords: exposure to cigarette smoke, low birth weight, meta-analysis. Correspondence:Winei Handriani. Master’s Program in Public Health, Universitas Sebelas Maret, Jl. Ir. Sutami 36A, Surakarta 57126, Jawa Tengah. Email: wineihandriani02@gmail.com. Mobile: 083150000253.